Pediatric Cyanide Poisoning After Ingestion of Apricot Seeds - Yüksel Bıcılıoğlu; İhsan Yıldırım; Pınar Yazıcı Özkaya; Alkan Bal (Galenos Yayinevi, 2020)
Cyanide is one of the strongest and lethal poisons. Cyanide leads to tissue hypoxia and lactic acid accumulation. Hydroxocobalamin is a safe, fast and effective antidote that could be used, especially in children. In this paper, we presented four cases of cyanide poisoning caused by apricot seed ingestion. Three of the patients were transferred to the paediatric intensive care unit, and hydroxocobalamin was given, and their conditions improved rapidly. This study aimed to draw attention to cyanide poisoning caused by apricot seed ingestion and to hydroxocobalamin use as an antidote.